2008
DOI: 10.1158/1055-9965.epi-07-2926
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Stability of Human Aflatoxin B1 Albumin Adducts Assessed by Isotope Dilution Mass Spectrometry and High-Performance Liquid Chromatography–Fluorescence

Abstract: The measurement of the aflatoxin B 1 -lysine serum albumin adduct in human blood samples is the most facile biomarker for the assessment of chronic exposure to aflatoxin B 1 . Many technologies have been developed for the measurement of this protein adduct including immunoassays, high-performance liquid chromatography (HPLC) with fluorescence detection, and a newly developed isotope-dilution mass spectrometry method. Irrespective of the technology used to determine this adduct level, an important question rema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(39 citation statements)
references
References 16 publications
0
38
0
1
Order By: Relevance
“…confirmed, 52 as well as their significant correlation with AFB 1 intake. 53 Measurement of the adduct levels in urine, however, provides a noninvasive means of estimating the levels of AFB 1 exposure, with a correlation of 0.65 found between total dietary AFB 1 intake and urinary AFB 1 extraction.…”
Section: Discussionmentioning
confidence: 55%
“…confirmed, 52 as well as their significant correlation with AFB 1 intake. 53 Measurement of the adduct levels in urine, however, provides a noninvasive means of estimating the levels of AFB 1 exposure, with a correlation of 0.65 found between total dietary AFB 1 intake and urinary AFB 1 extraction.…”
Section: Discussionmentioning
confidence: 55%
“…23 The authors have previously found that airborne ) in the Helwan district in Cairo, Egypt, and the concentration of Aspergillus flavus in the two workplaces was higher compared to that in the control area (11.5¡1.41 cfu/m 3 ). 8 Chronic occupational exposure to high concentrations of Aspergillus flavus was found to cause significant elevation in the serum AFB1/Alb of bakers and flourmill workers compared to the normal controls.…”
Section: Discussionmentioning
confidence: 93%
“…As a result of its longer in vivo half-life as compared with other urinary AFB 1 metabolites, such as AFM 1 and AFB-N 7 -guanine, the AFB-Lys adduct can reflect integrated exposures over 2-3m o n t h s . The long-term stability (up to 20 years) in frozen serum or plasma made this adduct a first choice of biomarkers to study human AF exposure and its link to diseases (Wang et al 1996;Wang, Abubaker, et al 2001;Scholl & Groopman 2008). Highly significant associations between AFB-Lys adduct level and dietary AFB 1 exposure have been found in human populations from several regions of the world.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, our study used archived serum samples in both cohorts. Even though the AFB-Lys adduct has been shown to have a long-term stability over 20 years under proper storage conditions (Wang et al 1996;Wang, Abubaker, et al 2001;Scholl & Groopman 2008), the repeated thaw and freeze cycle of these samples may degrade the adduct level in the original samples. Nevertheless, by using longitudinal study design and a more accurate detection method for AFB-Lys measurement, our study shows the constant AF exposure over 21 years and provides better estimates of AF exposure in central and south-western Ugandan populations.…”
Section: Round (Year)mentioning
confidence: 99%